2021
DOI: 10.3390/biology10020082
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Aspartame Administration Leads to Fibrosis, Inflammasome Activation, and Gluconeogenesis Impairment in the Liver of Mice

Abstract: Background: Aspartame is an artificial sweetener used in foods and beverages worldwide. However, it is linked to oxidative stress, inflammation, and liver damage through mechanisms that are not fully elucidated yet. This work aimed to investigate the effects of long-term administration of aspartame on the oxidative and inflammatory mechanisms associated with liver fibrosis progression in mice. Methods: Mice were divided into two groups with six animals each: control and aspartame. Aspartame (80 mg/kg, via oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…after 12 weeks, liver fibrosis, elevated liver enzymes and reduced enzyme antioxidant activity was proven. 21 Many other researches [22][23][24] have highlighted and supported our results regarding the hepatotoxicity, nephrotoxicity and oxidative stress on liver caused by aspartame. Liver protection trial has been commenced against drug deleterious effects using herbal remedies, 25 propolis, 26 vitamins, 27,28 and zinc as a mineral.…”
Section: Resultssupporting
confidence: 81%
“…after 12 weeks, liver fibrosis, elevated liver enzymes and reduced enzyme antioxidant activity was proven. 21 Many other researches [22][23][24] have highlighted and supported our results regarding the hepatotoxicity, nephrotoxicity and oxidative stress on liver caused by aspartame. Liver protection trial has been commenced against drug deleterious effects using herbal remedies, 25 propolis, 26 vitamins, 27,28 and zinc as a mineral.…”
Section: Resultssupporting
confidence: 81%
“…Aspartame may induce oxidative stress through both decreased antioxidative enzyme expression and increased reactive oxygen species production, which were determined in the ovary and granulosa cells. Fimanor et al presented that malondialdehyde lipid peroxide in the liver was significantly increased and the activities of SOD-2, CAT, and glutathione peroxidase were significantly decreased, leading to an imbalance of oxidative stress after aspartame intervention for 12 weeks [ 11 ]. Similar effects were observed in the heart [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread use, the safety of aspartame remains controversial [ 8 ]. Some recent studies have implicated the consumption of aspartame as being associated with impacts on human or rat physiological responses such as glucose intolerance [ 9 ], body fat distribution [ 10 ], and liver damage [ 11 ]. Although studies have suggested the adverse effects of aspartame consumption, they were primarily based on animal experiments, and data from human studies are scant [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aspartame-induced cellular changes in the hepatocytes, another study reported hepatic fibrosis in mice through oxidative stress due to the long-term administration of aspartame over 12 weeks at 80mg/kg/day (24). Conversely, the current study's dosage over 10 weeks of 50-250 mg/kg/day did not result in any change being found regarding the amount or distribution of collagen in any of the groups, neither through the HE staining nor with the trichrome staining.…”
Section: Discussionmentioning
confidence: 99%